2019
DOI: 10.15390/eb.2019.8413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feedback on Turkish Fourth-Grade Elementary School Students’ Fluent Writing Skills

Abstract: Bu araştırmada geri bildirimin ilkokul dördüncü sınıf öğrencilerin akıcı yazma becerilerine etkisinin belirlenmesi amaçlanmıştır. Araştırmanın çalışma grubu, Ankara ili Yenimahalle ilçesinde bulunan bir devlet ilkokulunun dördüncü sınıfında öğrenim gören 42 öğrenciden (21 deney grubu, 21 kontrol grubu) oluşmaktadır. Araştırmada veri toplama aracı olarak Akıcı Yazma Değerlendirme Rubriği, hikâye yazma konuları ve geri bildirim formu kullanılmıştır. Üç aşamada gerçekleştirilen çalışma sekiz hafta sürmüştür. Akıc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Furthermore, there are few studies that measure the effect of an activity or approach directly on students' spelling rules and punctuation marks. However, various research has revealed that feedback increases students' fluent writing success (Hier & Eckert, 2014;Koenig, Eckert & Hier 2016;Truckenmiller et al, 2014;Kaya et al, 2020). Black and William (1998) stated that feedback was very effective in the learning processes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are few studies that measure the effect of an activity or approach directly on students' spelling rules and punctuation marks. However, various research has revealed that feedback increases students' fluent writing success (Hier & Eckert, 2014;Koenig, Eckert & Hier 2016;Truckenmiller et al, 2014;Kaya et al, 2020). Black and William (1998) stated that feedback was very effective in the learning processes.…”
Section: Discussionmentioning
confidence: 99%
“…The text can be evaluated in terms of ideas and content, organization, paragraph formatting, voice and tone, word choice, sentence fluency, and conventions in the rubrics used. Finally, the effect of feedback on fluent writing was presented in Kaya et al (2020). Writing skill is acquired later and develops more complicated than the other three skills.…”
Section: Giving Feedback On Writingmentioning
confidence: 99%
“…Alanyazında dönütlerin öğrencilerin öğrenmelerini (Kaya, Ateş, Yıldırım & Rasinski, 2020) ve öz saygılarını (Çevikbaş & Argün, 2016;Kaya vd., 2020) olumlu yönde etkilediğini ortaya koyan çalışmalar mevcuttur. Öğrencilere her hafta raporlarının değerlendirilmesinden sonra topluca dönüt verilmiştir.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified